Effects of D-003, a Mixture of Very Long Chain Saturated Fatty Acids, and Policosanol on in vivo Lipid Peroxidation in Rats - Perez, Yohani; Más, Rosa; González, Rosa María; Jiménez, Sonia; Molina, Vivian (Arzneimittelforschung, 2008)
D-003 and policosanol (CAS 557-61-9), specific and distinct mixtures of high molecular weight primary aliphatic acids and alcohols, respectively, have shown to inhibit lipid peroxidation in vivo, but comparative studies between their effects on lipid peroxidation processes had not been conducted before.To compare the effects of D-003 and policosanol on markers of lipid peroxidation in vivo in rats.Male Wistar rats were distributed into 9 groups: a control group treated with acacia gum/water vehicle, 4 with policosanol and 4 with D-003, both treatments at 5, 25, 100 and 250 mg/kg. Treatments were administered during 4 weeks.Both treatments significantly and dose-dependently reduced plasma malondyaldehide (MDA) and total peroxides. Nevertheless, while D-003 was effective from 5 mg/kg, the lowest effective dose of policosanol was 25 mg/kg. The maximal effects of both treatments were obtained with 100 mg/kg, but greater in D-003 than in policosanol group, and the same occurred across all doses tested. MDA concentrations generated with the enzymatic system in liver homogenates were also significantly and dose-dependently inhibited with both treatments. The lowest effective doses of D-003 and policosanol were 5 and 100 mg/kg, respectively, and the highest inhibitions of about 80% (D-003) and 11% (policosanol). D-003 was more effective than policosanol in all comparisons. D-003 was also more effective than policosanol for lowering MDA concentrations generated with the no enzymatic system, but in these conditions policosanol was effective from 25 mg/kg and produced an inhibition somewhat greater (about 29%) than on MDA-generated by the enzymatic system. Both policosanol and D-003 did not modify the activity of endogenous antioxidant enzymes compared with the controls.D-003 (5–250 mg/kg) orally administered for 4 weeks was more effective than policosanol for lowering all the lipid peroxidation markers assessed, like plasma MDA and total peroxides, and MDA concentrations generated by the enzymatic and non-enzymatic oxidant systems of liver homogenates. The inhibitions with D-003 were marked and dose-dependent. Neither D-003 nor policosanol modified the activity of enzymes involved in the endogenic antioxidant defensive system.
Keywords: Antioxidants; CAS 557-61-9; D-003, effect on lipid peroxidation, rat; Fatty acids mixture, very long chain; Lipid peroxidation; Policosanol, effect on lipid peroxidation, rat